Integración de la energía eléctrica generada por biogás de Porcina Americana S.A. (PASA) al nuevo sistema de Generación Distribuida para Auto Consumo de JASEC y estudio de consumos/demandas de energía para su planta en Coris de Cartago - Segura-Rivera, Iván David (Instituto Tecnológico de Costa Rica, 2017)
Porcina Americana S.A., a company that breeds and processes pork, is the company that owns the largest bio-digestion generator in the country with a capacity of 250 kW. This is why, in this project, it is intended to bring the reader to know more in detail the processes that are performed there and mainly to know the current energy state in which the company is from an administrative and management perspective. It will demonstrate the actual consumption of the process plant as well as its demand values and energy generation statistics for the generator that is owned. Another of the objectives that are intended to be shown is the improvement in billing that implies the inclusion of a generation system to the regime of distributed generation for self consumption currently in force in Costa Rica
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2017.
Keywords: Consumo; Energía; Bio-digestor; Metano-génesis; Generador